Interaction, integration, and innovation at the 17th century feira of Dambarare, northern Zimbabwe - Schenck, Catherine (Department of Archaeology, 2018)
Several feiras (or trading towns) were established north and south of the Zambezi River towards the end of the 16th and early 17th centuries. Those feiras south of the Zambezi were mercantile and domestic settlements built by the Mutapa state and the Portuguese, and acted as points of contact between foreign and local traders. Dambarare, one of the more important feiras of the 17th century, was excavated in 1967 and the archive subsequently grew due to development activities in the region. In nearly fifty years, no-one has considered this archive as a whole, and few questions have been asked about the nature of the relationships between its inhabitants, and between them and their neighbours. The archival records are considered to better understand the site, and the objects are approached by considering their ability to show multivocality and entanglement at a site where various people were converging. The themes of interaction, integration, and innovation at this contact site are put to the fore in this dissertation. The results of the study point to a much more complex settlement and manner of interaction than previously understood. It does not seem as though changes and adaptations were brought on by force from one group at the site, but rather choices were deliberate, whether by choice or necessity. These interactions indicate a complex negotiation and creolisation that occurred between the various identities at the feira. These interpretations then fit into a larger attempt in the archaeology of the region to better understand the role of hinterland communities in the Indian Ocean Trade System, and to change existing opinions of such sites and their peopling. This dissertation attempts, therefore, to show that at a Zambezian hinterland site such as Dambarare, people were not merely passive receptors, but rather active agents in the changes that occurred, as well as causing their foreign counterparts to adapt to them.